P250 PROTOCOL FOR TELEHEALTH EVALUATION AND FOLLOW–UP OF PATIENTS WITH CHRONIC HEART FAILURE DURING THE COVID–19 PANDEMIC. (18th May 2022) - D'Errico, G; Herbst, A; Orso, F; Baldasseroni, S; Fattirolli, F; Virciglio, S; Camartini, V; Di Bari, M; Marchionni, N; Ungar, A; Salucci, C; Verga, F
Abstract: Background: After the lockdown imposed by the COVID19 pandemic, physicians had to limite ambulatory visits to exceptional cases to reduce interpersonal contact. We structured a telephone follow–up developing a standardized 23 item questionnaire to administrate to our HF outpatient clinic and from whom we obtained the Covid–19–HFscore. Methods: The patients were identified by a numeric code, date of birth and gender. The questionnaire was designed for rapid administration during telephone interview (on average 6 minutes) and was administered directly by physicians to patients and/or to their caregiver. It was built to reproduce our usual clinical evaluation. Results: As shown in Figure 1, we investigated seven domains: 1) social and functional condition 2) mood 3) adherence to pharmacological and non–pharmacological recommendations (blood pressure, heart rate, weight monitoring and fluid intake control) 4) clinical and hemodynamic status 5) recording of laboratory tests 6) current pharmacological treatment 7) recent evaluation by family physician or need to contact emergency services followed or not by hospitalisation. General and pharmacological recommendations as well as the following telephone contact were finally recorded. To determine the timing of the next telephonic evaluation, we decided to weight questions regarding clinical and hemodynamic status, adherence to pharmacological and non–pharmacological recommendations, therapeutic changes and need for hospitalisation by scoring the answers (from 1 to 3) to build a score. The sum of individual scores represented the novel TeleHFCovid19–score, ranging from 0 to 29. Based on such score, three groups of patients were identified by arbitrary cut–off levels: the green (score <4), the yellow (score 4–8) and the red (score ≥9) group, for which next telephonic evaluation was planned respectively after four, two and one week respectively. Alternatively, the red group could receive recommendation for urgent hospital evaluation. Conclusion: During this emergency situation this questionnaire could be a useful clinical tool to help physicians maintaining a regular FU of their patients and identifying patients at greatest risk of imminent instability. Furthermore, this instrument could also represent a useful resource in the management of low–risk HF patients.